1999
DOI: 10.1007/s002109900137
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of endothelin-1 to disruption of blood-brain barrier permeability in dogs

Abstract: We examined the effect of intracisternal application of endothelin-1 (ET-1) on the permeability of fluorescein into the cerebrospinal fluid (CSF) in beagle dogs in order to evaluate its role in disruption of blood-brain barrier (BBB) permeability seen in the subarachnoid hemorrhage animal model. Intracisternal application of their autologous blood for producing a canine two-hemorrhage model revealed an enhanced fluorescein permeability into the CSF together with the development of cerebral vasospasm. A single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Another vascular hypothesis to investigate is related to the question of whether disruption of the blood-brain barrier (BBB) by ET-1 may promote the induction of CSD. Consistently, similar to vasoconstriction, BBB opening by ET-1 is mediated via ET A receptors (44,57). Furthermore, it has recently been shown that BBB disruption causes changes in neuronal excitability (53).…”
Section: Csd-like Depolarizations and A Penumbra-like Conditionmentioning
confidence: 80%
“…Another vascular hypothesis to investigate is related to the question of whether disruption of the blood-brain barrier (BBB) by ET-1 may promote the induction of CSD. Consistently, similar to vasoconstriction, BBB opening by ET-1 is mediated via ET A receptors (44,57). Furthermore, it has recently been shown that BBB disruption causes changes in neuronal excitability (53).…”
Section: Csd-like Depolarizations and A Penumbra-like Conditionmentioning
confidence: 80%
“…Significant BBB opening was found by Narushima et al (47) after intracisternal ET-1injection, considerably potentiated by a second injection. Several papers report that ET-1 stimulates COX-2 induction.…”
Section: Pro-inflammatory Effects Of Etsmentioning
confidence: 85%
“…ET-1 release has been shown to occur in many CNS disorders, including cerebral vasospasm/subarachnoid hemorrhage, stroke, human immunodeficiency virus encephalitis/ AIDS dementia complex, multiple sclerosis, and other inflammatory diseases of the brain (Levin, 1995;Nie and Olsson, 1996;Brooks et al, 1998;Narushima et al, 1999;Kedzierski and Yanagisawa, 2001;Didier et al, 2002). The literature contains conflicting reports as to the effects of ET-1 on brain capillary permeability.…”
Section: Regulation Of P-glycoprotein At the Blood-brain Barrier 391mentioning
confidence: 99%